The credibility of regional policymaking: insights from South America. Issue 4 (19th May 2022) - Riggirozzi, Pia; Ryan, Matt
ABSTRACT: Regional responses to international threats and opportunities have become prevalent. Yet significant lacunae persist in our recognition of some impacts of regional policies. Where measuring impact of regional policy does exist, this tends to focus on economic impact, heavily influenced by the EU model, or focuses on impacts that we have come to expect from national level policymaking. In this paper we show that important effects of regional policymaking in South American regionalism are being overlooked. Specifically, we argue that failure to recognize the creation of normative frameworks, dynamics of regional diplomacy, and social policy outcomes from regional policymaking has negatively affected the credibility of regional organizations. Lack of understanding of the impact of regional policy risks trivializing progress in regional policy and, critically, affects the legitimacy and credibility of regional governance. We make this case by focusing on regional health and migration policies in South America.